Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Pada Perusahaan Perdagangan Sub Sektor Grosir Yang Terdaftar Di Bursa Efek Indonesia - Rini Rini; Iffahana F. Amelinda; Khusnul Khoatim; Lui Lestari; Nabila H. Putri (Universitas Veteran Bangun Nusantara, 2023)
Effective Intellectual Capital enhances the strategic advantage of companies in an increasingly competitive business world and drives them towards achieving better financial performance. This research aims to evaluate the influence of intellectual capital on the performance of wholesale companies in Indonesia from 2020 to 2022. The uniqueness of this study lies in exploring the impact of intellectual capital on the performance of wholesale companies in Indonesia, an aspect that has not been previously investigated. The analysis method employed in this research utilizes secondary data. The analytical techniques include classical assumption tests such as normality test, heteroscedasticity test, and autocorrelation test, linear regression analysis, and one-way ANOVA. Data is collected from the financial reports of companies available on the Indonesia Stock Exchange. Non-probability sampling using purposive sampling technique is employed in this study. The initial sample consists of 47 companies over a three-year period, from 2020 to 2022, and the final sample represents approximately 40.42 percent of wholesale companies that meet the criteria during the research. The research findings indicate that Intellectual Capital significantly and positively affects financial performance, Return on Asset (ROA) in Wholesale Companies listed on the Indonesia Stock Exchange from 2020 to 2022. The improved capabilities of human resources are expected to generate favorable performance for the companies, resulting in increased profitability measured by Return On Asset.